STRATEGI PROMOSI DALAM MEMBANGUN BRAND MEDIA MANDIRI (STUDI KASUS DONATUR MEDIA MANDIRI) - Rosmalah D.K, Kartini (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
Media Mandiri is a new brand of service marketing which offers scholarship in the field of proselytizer and entrepreneurship. The interesting thing is that the marketing communication used to promote is the students who had the scholarship, their responsibility as the personal selling team of Media Mandiri are searching for the donor. The objective in this research is to find out promotion strategy to build brand of Media Mandiri. The theory used in this research is IMC and Brand Equity by David A. Aaker. Paradigm in the research is constructivist. Meanwhile, the method used is qualitative single case study that is donors of Media Mandiri. The result of study: (1) Time conditional: by personal selling (presentation) and advertising in the form of the distribution of brochures during the presentation and dissemination outlets to shops and restaurants. Now, the Media Mandiri  indirectly does brand awareness, brand association, and brand loyalty to the donors. (2) Time temporal: the spread of advertising (piggy bank) and sales promotion (keychain) in the month of Ramadan. While Khataman Quran recitation event conducted in accordance with the request of donors, so it is temporary only. In this promotional activity, Media Mandiri are doing perceived quality and brand loyalty to the donors. That is how the quality of the impression formed donors see the Media Mandiri, so it is showed that brand loyalty on the part of donors to the Media Mandiri